Environmental Education in Children with Special Educational Needs. Challenges and Development Perspectives - Llopiz Guerra, Karel (2020)
In the new century, the leading role of education as a social and transformative phenomenon for the survival of the human species is urgent, in response to the emergence of environmental problems as a result of the aggressive interaction of man with natureand the society in which he develops, with the existence of serious ecological problems expressed in the worsening of the environment caused by natural events and disasters, the irrational exploitation of natural resources, the increase of industrialization, excessive urbanization, migration and the population explosion.